Changing Visions of Heritage Value: What Role Should the Experts Play? - Silberman, Neil (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The author of this paper questions the role of the experts in heritage policies and practices. Is the voice of the heritage expert now guided by the vox populi? The current evidence for these trends, long considered anathema to heritage purists, suggests that an epoch-making change in heritage practice is now underway. The announcement of a Memorandum of Understanding between the World Bank and UNESCO to provide “very positive input for the improvement of aid effectiveness, and make the most of culture as a motor for social development and poverty alleviation, through employment and job creation” and the theme of the 17th ICOMOS General Assembly, “Heritage, a Driver of Development” are both clear indications of a pressing new concern: that heritage contribute to the economic – not only cultural – well-being of contemporary society. No less significant is the emphasis on public rights and responsibilities in the formulation of heritage policy, once the exclusive prerogative of antiquarians and professional conservators. This turn to the public as full-fledged heritage stakeholders is expressed clearly by the Council of Europe’s Framework Convention on the Value of Cultural Heritage for Society (2005) and the efforts of UNESCO to promote the active participation – and economic advancement – of traditional practitioners of intangible cultural heritage.